Studies of mathematics at the beginning of higher education reform - Kaminskienė, Janina; Rimkuvienė, Daiva; Laurinavičius, Eligijus (Lietuvos matematikos rinkinys, 2010)
The article discusses problems of mathematics teaching at Lithuanian University of Agriculture at the beginning of reform of higher education. Quite a high percentage of students lack background of mathematics and don‘t have the skills to work independently, while their parents are able to pay the full price of studies. Students’ motivation and enrolment into universities also raises many problems. In response to reported problems teaching of mathematics the additional measures of organization teaching are proposed.